X-ray images of laying hens - Mohammed Abdallah, Sallam; Göransson, Lina; Larsen, Anne; Gunnarsson, Stefan; Wall, Helena; Johnsson, Martin; De Koning, Dirk-Jan (Swedish University of Agricultural Sciences, 2024)
The dataset contains x-ray images of birds (laying hens) that were generated during the research project funded by Svenska Forskningsrådet Formas (2019-02116). The project aimed to develop a digital tool to assess bones of laying hens using x-ray imaging. The dataset contains a total of 1,116 images, of 168 birds, each bird was x-rayed several times: 3-5 times during their life, 1 time post-mortem, and 1 time for its dissected tibia and keel bones. All images are in JPEG format. All images are named with informative codes indicating bird id, date and time of x-raying, whether the image for live or postmortem x-raying. More details are provided in the attached README file.

Datasetet innehåller röntgenbilder av fåglar (värphöns) som genererades under forskningsprojektet finansierat av Svenska Forskningsrådet Formas (2019-02116). Projektet syftade till att utveckla ett digitalt verktyg för att bedöma benen hos värphöns med hjälp av röntgenavbildning. Datasetet innehåller totalt 1 116 bilder av 168 fåglar. Varje fågel röntgades flera gånger: 3-5 gånger under sin livstid, 1 gång post mortem och 1 gång för dess dissekerade tibia- och bröstbensben. Alla bilder är i JPEG-format och namnges med informativa koder som anger fågelns id, datum och tid för röntgenundersökningen samt om bilden är tagen för levande eller post mortem-röntgen. Mer detaljer finns i den bifogade README-filen.
Röntgenbilder av värphöns
Keywords: X-ray; röntgenstrålning; Animalia; flercelliga djur; Chordata; ryggsträngsdjur; keel bone; bröstbens; Laying hens; Värphöns; x-ray images; x-ray-bilder; commercial layers; Kommerciella värphöns; Aves; Pangalliformes; Gallus Galliformes; Agricultural Science; Jordbruksvetenskap; Veterinary Science; Veterinärmedicin; Animal and Dairy Science; Husdjursvetenskap